Demonstrating backflow in classical two beams’ interference - Anat Daniel; Bohnishikha Ghosh; Bernard Gorzkowski; Radek Lapkiewicz (New Journal of Physics, 2022)
The well-known interference pattern of bright and dark fringes was first observed for light beams back in 1801 by Thomas Young. The maximum visibility fringes occur when the irradiance of the two beams is equal, and as the ratio of the beam intensities deviates from unity, fringe visibility decreases. An interesting outcome that might not be entirely intuitive, however, is that the wavefront of such unequal amplitude beams’ superposition will exhibit a wavy behavior. In this work, we experimentally observe the backflow phenomenon within this wavy wavefront. Backflow appears in both optics (retro- propagating light) and in quantum mechanics (QM), where a local phase gradient is not present within the spectrum of the system. It has become an interesting subject for applications as it is closely related to superoscillations whose features are used in super resolution imaging and in a particle’s path manipulations. The first successful attempt to observe backflow was made only recently in an assembly of optical fields, by synthesizing their wavefront in a complex manner. Yet, backflow is perceived as hard to detect. Here, by utilizing interference in its most basic form, we reveal that backflow in optical fields is robust and surprisingly common, more than it was previously thought to be.